Dyspnea Pada Penderita Asma Dengan Teknik Pernafasan Buteyko - Alya Meivianora; Amelia Tasya; Mita Suryaningsih; Tria Wahyuni; Novita Elisabeth Daeli (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Asthma is a chronic disease characterized by airway hyperactivity due to inflammation and reversible airflow obstruction. The most common triggers of asthma are allergies (food or inhalants such as dander, dust, pollen), exposure to cold temperatures, and upper respiratory infections. Non-pharmacological therapy can be carried out with the buteyko breathing technique which aims to reduce dyspnea, asthma attacks, wheezing, reduce symptoms of nasal congestion and stop coughing experienced by sufferers. The purpose of this study was to determine the effectiveness of buteyko exercise on dyspnea symptoms in asthma sufferers. The research method used was a pre-experimental one group pretest-posttest to see differences in the dyspnea scale in the intervention group before and after the buteyko exercise. The results of the pre-test and post-test statistics p = 0.025 <0.05 where there were differences in the dyspnea scale after being given buteyko exercises. Prior to the Buteyko exercise, it was shown that 4 respondents (40%) had mild dyspnea, 4 respondents (40%) had mild, 2 respondents (20%) were mild. After doing the buteyko exercise, it was shown that 7 respondents (70%) had mild dyspnea, 3 respondents (30%) had mild symptoms. Research shows that there is a decrease in the level of dyspnea after being given buteyko exercises with an average dyspnea scale decreasing (negative rank) with a result of 3.00. It was concluded that there were differences in the dyspnea scale after being given buteyko exercises, that there were significant results for a decrease in the dyspnea scale in asthma sufferers.